Nitrogen deposition mitigates long-term phosphorus input-induced stimulative effects on soil respiration in a tropical forest - Huang, Xingyun; Li, Yingwen; Yu, Shiqin; Cui, Yongxing; Guan, Fangyuan; Li, Yongxing; Wu, Jingtao; Hu, Yang; Li, Zhian; Zhuang, Ping; Zou, Bi; Qin, Guoming; et al. (Geoderma, 2025)
•Long-term phosphorus input enhanced soil respiration (RS) and heterotrophic respiration (RH)•Nitrogen deposition mitigated the stimulative effect of phosphorus input on RS by reducing RH.•Long-term phosphorus input decreased autotrophic respiration (RA) by reducing plant litter input.•Nitrogen deposition mitigated RH by decreasing plant litter, carbon quality, and fungi biomass. Atmospheric nitrogen (N) deposition and anthropogenic phosphorus (P) input simultaneously affect soil respiration (RS), a crucial process that mediates soil carbon (C) cycling. However, the interaction of N deposition and anthropogenic P input on RS, as well as its components—autotrophic respiration (RA) and heterotrophic respiration (RH)—remain largely unexplored. Herein, we conducted an 8-year field experiment with N and P additions in a tropical secondary forest, integrating the vegetation traits, soil physicochemical properties, organic C fractions, and microbial properties, to explore the effects of nutrient inputs and their interactions on RS, RA, and RH. Over eight years, along P input significantly increased RS by 19.2% and RH by 42.1%. These increases were partially mitigated (by 33.2% annually for RS and 58.3% annually for RH) with the addition of N. In contrast, the co-addition of N and P enhanced RA compared to alone N or P addition, suggesting that N deposition mitigated the stimulative effect of P input on RS by reducing RH rather than RA. The structural equation model further revealed that N deposition reduced RH primarily by increasing soil N:P ratio and decreasing both the labile C fraction and fungi biomass. Our findings suggest that prevalent N deposition across low latitudes could have substantially mitigate C emissions from forest soils under anthropogenic P input.